Legal Implications of Inherited Land Certificate Split: A Review of Agrarian Law and Inheritance Law Perspectives - Aisyah, Aisyah (Ipso Jure, 2025)
The breakdown of inherited land certificates in Indonesia faces serious challenges due to the insynchronization between the monistic agrarian legal system and the pluralistic inheritance law (civil, Islamic, and customary). This dualism creates normative and administrative barriers, especially when the process of renaming a certificate requires formal legal documents, while many societies still use a deliberation or customary-based non-formal inheritance system. This study aims to analyze the legal inconsistencies and the need for regulatory harmonization between agrarian law and inheritance law in the context of inherited land redistribution. Using normative juridical methods and legislative, conceptual, and case-case approaches, this study found that the absence of legal instruments recognizing the validity of non-notarial inheritance documents has triggered many inheritance land disputes. Weak legal accessibility and maladministrative practices further worsen the protection of civil rights of the community. Therefore, there is a need for a policy reformulation based on legal pluralism and responsive law that is able to accommodate social realities and ensure substantive justice. Strengthening the role of notaries, PPAT, and recognition of customary inheritances are strategic steps in building an inclusive, fair, and democratic land system. These findings are expected to be an important contribution to the national agrarian reform agenda based on justice and legal certainty.